Evaluation of simulation skills of healthcare workers at a tertiary care center: A perspective towards coronavirus disease 2019 (COVID-19) third wave preparation - Sudha Bala; Aruna K Yerra; Sushma Katkuri; Karuna S Podila; Venkatesham Animalla (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Simulation-based training for healthcare providers was established as an efficacious training tool to sharpen the performance skills of nontechnical team as necessary for the prevention of errors and adverse events in the pandemic. To tackle this third wave, our institute started preparations with a faculty development course of simulation-based learning to evaluate participants' knowledge and skills and their attitudes and feedback. MATERIALS AND METHODS: As part of the simulation workshop, a module was developed to train the staff on recognizing and responding to acute coronavirus disease 2019 affecting adults and children. Case-based scenarios were provided in the application. Pretest and posttest questionnaires were administered to all trainees. The questionnaires included questions on knowledge, skills confidence and attitude marked on a 5-point Likert scale. Data were entered and analyzed using the Microsoft Excel 2018. Qualitative variables were expressed as percentages, whereas mean and standard deviations were computed for quantitative variables. Paired t-test was used to test the difference between pre and post test scores; P < 0.05 was taken as significant value. RESULTS: A total of 296 participants were included in the study. A statistically significant increase in knowledge and skills confidence scores was found from pre-test to post-test. The most significant improvement was found in the assessment of pediatric hemodynamic status and the management of fluid and electrolytes. The most interesting benefit to the participants was the acquisition of knowledge about the proper use of technology after the faculty development course. CONCLUSIONS: Such workshops play a crucial role in training healthcare workers, especially as preparation for the pandemic. Most participants suggested that there should be such workshops at regular intervals to enhance their skills confidence in handling emergency situations in the clinical settings.